Difficulties in Diagnosing a Patient with Fever of Unknown Origin - E. I. Fomina; E. E. Gubernatorova; T. V. Adasheva; T. V. Baturina; P. S. Samoszhenova; N. U. Timofeeva (SINAPS LLC, 2024)
Fever of unknown origin is a difficult syndrome for differential diagnosis. Absence of a key feature, variety of causes and the lack of single examination algorithm makes difficult further diagnosis. The presented clinical case describes a 53-year-old patient with a prolonged fever of more than 1.5 months, pain syndrome in the facial area. During outpatient monitoring, the cause was not clarified. At the inpatient stage, a comprehensive examination was conducted for all classes of causes. The revealed changes in the thyroid gland and thyrotoxicosis made it possible to diagnose subacute thyroiditis. According to the literature, subacute thyroiditis is one of the rare causes of fever of unknown origin. Prescription of glucocorticosteroid made it possible to achieve complete regression of clinical symptoms in 4 days. After 5 months, subclinical hypothyroidism was achieved. The nosological approach and multidisciplinary interaction contributed to the correct tactics and a favorable outcome of the disease.